Compression Stockings versus Neuromuscular Electrical Stimulation Devices in the Management of Occupational Leg Swelling - Wou, J.; Williams, K. J.; Davies, A. H. (International Journal of Angiology, 2016)
Background Occupational edema is reported to occur in healthy individuals after working in a sitting or standing position for extensive periods of time. It can be associated with feelings of tiredness, heaviness of the legs, and pain. Three licensed medical devices were compared in their management of occupational edema.Subjects and Methods A total of 10 subjects were recruited from a clinical workspace. Right leg volume and great saphenous vein diameter was measured in the morning, and 6 hours later. On subsequent separate days, grade 2 graduated compression stockings (Active Compression Socks, Mediven, United Kingdom), geko (Firstkind Ltd, United Kingdom), and Revitive (Actegy Ltd, United Kingdom) were used bilaterally according to manufacturer's instructions.Results Leg volumes increased by median 41 mL (p < 0.05) with no intervention. Percentage increase in leg volume was found to be significantly reduced by stockings compared with control (−1.7%, p < 0.01), and were more effective than electrical devices. Changes in vein diameter poorly correlate with leg volume changes.Conclusion Occupational edema can occur over as little as 6 hours. All devices were well tolerated and reduced leg swelling. Stockings were the only device to significantly reduce leg swelling in this small trial.
Keywords: swelling; leg; edema; electrical stimulation; NMES; compression